Hiperentorno educativo para el aprendizaje de la informática y el proceso investigativo de las carreras de tecnología de la salud. - Font, Isabel Legrá; Rodríguez, Gustavo Moll; Montoya, Zenaida Ramón (MEDISAN, 2014)
An educational software, of hyperentorno type was designed to develop the teachinglearning processes in the subjects Computer science and Investigation of the health technology careers from June, 2011 to the same period of 2013. Scientific methods were applied to corroborate the real state of knowledge and skills on the aspects contained in this software, which was structured in different modules: Agenda, Exercises, Glossary, Mediateca, Complements, Games and Helps, with interrelations between them, allowing the development of learning. In its elaboration several design programs were used, but the CrheaSoft 2.2 constituted the main tool for its implementation.